Source characterization guidelines for noise mapping of port areas. Issue 3 (March 2022) - Fredianelli, Luca; Gaggero, Tomaso; Bolognese, Matteo; Borelli, Davide; Fidecaro, Francesco; Schenone, Corrado; Licitra, Gaetano
Abstract: Maritime transport for both passengers and freight is continuously increasing and, consequently, the global attention toward its sustainability is growing. Ships offer advantages in terms of environmental impact compared to other transportation systems but the increasing traffic volume is expected to increase pollutants. Noise produced in port areas has been neglected for too long, until the INTERREG Maritime programme Italy-France 2014–2020 has brought to light how citizen complaints are emerging for some of the main ports in the Mediterranean. However, port noise prevention and management is difficult as knowledge on specific sources is very limited in the literature. Furthermore, on field measurements are difficult to be performed given the complexity of the port area, where multiple types of sound emitters mix and confuse each other. Noise maps represent the first important step in order to align ports to the requirements set by the Environmental Noise Directive to the transportation infrastructures. Once computed, they are an excellent tool supporting port management towards the reduction of citizens' noise exposure while ensuring traffic growth. The present paper reports a guideline for the characterization of noise sources needed as inputs for the noise maps, as developed in the framework of the INTERREG Maritime programme Italy-France 2014–2020. On the basis of the current state of the art, a procedure has been elaborated for different categories of noise sources acting in port, ranging from stationary to moving ships, from mooring operations to loading/unloading operations, from industrial activities to road and railway traffic. Abstract : Port noise; Guidelines; Sources characterization; Interreg maritime programme; Noise of transport infrastructures.